Upaya Meningkatkan Hasil Belajar PAI Melalui Metode Diskusi Pada Siswa Kelas XII SMA Plus Arraudah - Qolbi, Silmi Nurul Fitri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In implementing learning methods, educators are required to be able to align the object being taught, the methods used, and the material delivered, as these aspects greatly influence the learning process and the success of teaching students. The more effective the method, the more effective the learning process will be. The purpose of this research is to examine how the implementation of the discussion method can improve student learning outcomes in the subject of Islamic Religious Education (PAI). This study is a Classroom Action Research (CAR) with the sample being twelfth-grade students of SMA Plus Arraudah. Data collection techniques were carried out through learning outcome tests, observation of student activities, and field notes. The success indicator was determined if at least 75% of students achieved scores above the Minimum Mastery Criteria (KKM). The results of the study showed that the application of the discussion method was able to significantly improve student learning outcomes in each cycle. At the pre-cycle stage, the level of student mastery was 17.4%, then in the first cycle it increased to 60.87%, and in the second cycle it rose again to 86.96%. Thus, it is proven that the implementation of the discussion method in PAI learning in grade XII was effective, with student learning outcomes improving significantly.